Applying a nutrition security lens to the Dietary Guidelines for Americans to address metabolic health - Volek, Jeff S.; Clinthorne, Jonathan; S. Yancy Jr, William (Frontiers in Nutrition, 2023)
Nutrition security - access to food that promotes well-being and prevents or treats disease, particularly among racial and ethnic minority populations, lower income populations, and rural and remote populations - is a national priority. Leading causes of death and disability in America, such as heart disease, stroke, cancer, and diabetes that disproportionately affect minorities are linked to preventable diet-related risk factors. Mounting evidence indicates that adherence to a lower-carbohydrate dietary pattern is associated with weight maintenance, improved blood glucose and insulin control, lower blood pressure, reduced markers of inflammation, and a more favorable lipid profile. Additionally, prior concerns regarding the higher fat and cholesterol content of this dietary pattern are less founded in modern research. The inclusion of a lower-carbohydrate option that meets all essential nutrient requirements aligns with the contemporary movement toward more flexibility and precision nutrition. Most important, a lower-carbohydrate option positions the Dietary Guidelines for Americans to more accurately reflect the current scientific evidence and more effectively address the metabolic health of the nation. Further, it has the potential to improve nutrition security by addressing metabolic diseases that disproportionately affect people from historically marginalized racial, ethnic, socioeconomic, and cultural backgrounds. Given that most American adults are living with at least one diet-related chronic metabolic disease, updating the Dietary Guidelines for Americans to recognize and reflect the poor health status of the general population is prudent and urgent.